2017
DOI: 10.1177/0956797617708634
|View full text |Cite
|
Sign up to set email alerts
|

As You Sow, So Shall You Reap: Gender-Role Attitudes and Late-Life Cognition

Abstract: Some studies have found that women outperform men in episodic memory after midlife. But is this finding universal, and what are the reasons? Gender differences in cognition are the result of biopsychosocial interactions throughout the life course. Social-cognitive theory of gender development posits that gender roles may play an important mediating role in these interactions. We analyzed country differences in the gender differential in cognition after midlife using data from individuals age 50 and above ( N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 50 publications
8
32
0
Order By: Relevance
“…NHANES cancer survivors with complete information on handgrip strength, cognitive function and other characteristics were included in the analyses. Descriptive characteristics were analysed separately in men and women, due to the documented gender difference in muscle strength [ 22 ] and cognitive function during later-life [ 23 ]. We summarized weighted means and standard errors for continuous variables, weighted proportions for categorical variables, and provided explorative P- values for gender comparison.…”
Section: Methodsmentioning
confidence: 99%
“…NHANES cancer survivors with complete information on handgrip strength, cognitive function and other characteristics were included in the analyses. Descriptive characteristics were analysed separately in men and women, due to the documented gender difference in muscle strength [ 22 ] and cognitive function during later-life [ 23 ]. We summarized weighted means and standard errors for continuous variables, weighted proportions for categorical variables, and provided explorative P- values for gender comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Gender roles affect the way women and men engage in education, the labour market, domestic and care work, and health behaviours (Loretto and Vickerstaff 2015;Courtenay 2000;Haberkern et al 2015). Additionally, they affect the design of formal institutions and policies, constraining or incentivising individuals' choices throughout the life course (Bonsang et al 2017;Bird and Rieker 2008). Social explanations for gender inequalities in health stress the relevance of health behaviours, such as tobacco and alcohol consumption, dietary habits, physical activity, and healthcare utilisation (Oksuzyan et al 2010;Mahalik et al 2007;Luy 2003), socio-economic factors, such as financial resources and working conditions (Read and Gorman 2011), and psychosocial factors, such as critical life events, social network characteristics, and coping styles (Thoits 2011;Lachman et al 2011).…”
Section: (Social) Explanations For Gender Inequalities In Healthmentioning
confidence: 99%
“…Results from this meta-analysis also indicated that the magnitude of these differences had remained stable since 1973 and that, for verbal tasks, the sex difference was somewhat smaller in childhood and old age than for other ages. Although the underlying mechanism for these sex differences are poorly understood, they have been reported in most of the examined countries (Bonsang et al, 2017;Asperholm et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%